Exploring Reasons for Digitalization Not Percolating into the Power Sector to the Extent Expected in India and Suggesting a Framework to Expedite the Same - Pothala, Koteswara Rao (Digital Repository of Theses - SSBM Geneva, 2024)
Digitization, digitalization, or digital transformation represents an essential convergence of IT and OT (Operational Technology) crucial for various industries, including the power sector. This paradigm shift not only enhances business competitiveness but also fosters improved safety, reliability, and sustainability while reducing costs and errors. Digitalization reduces costs to one-third in fuel and one- fifth in operations and maintenance. Digitalization‘s role in integrating physical and digital realms, optimizing processes, and enhancing overall performance within the power sector is very evident. Despite these obvious benefits, digitalization in the power sector, particularly in India, has not percolated to the anticipated extent. This research aims to delve into the reasons behind this shortfall, focusing on six key areas: strategy, operational excellence, regulatory landscape, technology, innovation, and economic considerations, collectively termed as 'SORTIE'. Additionally, it proposes a framework to expedite digitalization adoption by addressing these reasons. Through showcasing the effectiveness of the SORTIE framework in transitioning from trials to successful implementation, this study underscores the urgency and potential of digitalization in revolutionizing power generation. By identifying and overcoming barriers to digitalization deployment, this research aims to drive significant change, inform strategic decision-making, and shape the future trajectory of the power sector towards sustainability and resilience in an increasingly digitized world.